In vitro cytotoxic effect of PARP inhibitor alone and in combination with nab-paclitaxel on triple-negative and luminal A breast cancer cells - ÖZBAŞ, SUNA (SPANDIDOS PUBL LTD, 2018)
In the present study, the in vitro cytotoxic effect of poly(ADP-ribose) polymerase (PARP) inhibitor alone and in combination with nab-paclitaxel was evaluated on human triple-negative breast cancer (TNBC) cell line MDA-MB-231 and human luminal A breast cancer cell line MCF-7. For this purpose, cell index (CI) values obtained from xCELLigence Real-Time Cell Analysis (RTCA) DP instrument, mitotic index (MI), labelling index (LI) and apoptotic index (AI) analysis among cell kinetic parameters were used. As a result of PARP inhibitor application, there was a significant decrease in CI, MI and LI and a significant increase in AI for all the experimental groups. After application of PARP inhibitor in combination with nab-paclitaxel, the CI values were decreased for both cell lines, and the differences between the control and all the experimental groups were statistically significant (P<0.01) for all applications. PARP inhibitor, alone or in combination with nab-paclitaxel offers a promising treatment modality in different breast cancer subtypes.
Keywords: poly(ADP-ribose) polymerase inhibitor; nab-paclitaxel; MCF-7; MDA-MB-231; xCELLigence Real-Time Cell Analysis DP instrument; CHEMOTHERAPY; SUBTYPES; CHEMOSENSITIVITY; MICROTUBULES; GEMCITABINE; FORMULATION; PROGNOSIS; CISPLATIN; TARGETS; ALBUMIN